Peran Guru dan Orang Tua dalam Peningkatan Motivasi Belajar Siswa di Mi MUH Nogosari Kulon Progo - Ludimin (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
Roles of teachers and parents in raising motivation of students of islamic elementary schoolof muhammadiyah nogosari kulon progo. The purpose of this study are. (1) the role of teachers in improving student' motivation in Ma'arif Kediwung Islamic elementary schools. Secondly; (2) the role of parents in increasing learning.Motivation their children. The desaign of qualitative research. Informants in this study were principal’s, teachers, and parents Ma'arif Kediwung Islamic elementary school. which consists of one principal, nine teachers and fivety five parents. The collecting data using interview and observation techniques. The analysis data using interactive model Miles and Huberman. The results showed that teachers play a role in increasing students' motivation especially in: (a) as a motivator / donor support, (b) to creating conducive situation on learning, (c) move to their students, (d) to create good competition, (e ) apveag reward to their student (f)the student know their achievement, (g) choul be inspiration, (h) to give a gift. The role of parents in raising their children at home motivation is the role of parens are: (a) supporting their children , (b) ordering their children, (c) to create conducive situation in learning (d) giving rewards